Monitoring the impact of COVID-19 in Myanmar: Urban food retailers - Early July 2020 survey round - Masias, Ian; Goeb, Joseph; Lambrecht, Isabel B.; Maredia, Mywish K.; Win, Khin Zin (International Food Policy Research Institute, 2020)
Traditional family owned retail shops are the backbone of Myanmar’s consumer market. As the final node in the grocery supply chain, they sell all types of dry foods, i.e., processed and packaged, condiments, snacks, and beverages to final consumers. To some extent, they also supply basic staple grains, i.e., rice and pulses; dairy products; eggs; kitchen crops; and tobacco and alcohol. About 85 percent of all consumer goods in Myanmar are sold through these shops. In the food and grocery sector, these retail outlets, including wet markets, account for 90 percent of all sales, with the other 10 percent accounted for by fast-growing supermarkets. Because of the importance of traditional retail outlets in the last mile delivery of a wide variety of foods to consumers, any challenges they encounter from the COVID-19 crisis and corresponding policy responses to contain the virus have important implications for the availability and affordability of food for final consumers. This policy note is the first in a series of reports presenting results from rounds of a telephone survey of a sample of owners or managers of food retail shops located in the two largest cities in Myanmar, Yangon and Mandalay. The phone surveys are designed to provide a better understanding of the effects of COVID-19 shocks on Myanmar’s agri-food marketing system through the perspective of small-scale food retailers in urban areas. This policy note focuses on the demand side and overall business effects of the COVID-19 crisis on these food retailers. Phone interviews were conducted with 426 retail shop owners or managers between 8 and 15 July 2020. Eighty percent of those surveyed were in Yangon, with the rest in Mandalay.